The Effectiveness of Interactive Storytelling through Learning Videos in Improving Elementary Students’ Listening Skills - Sindy Ashari; Erwin Eka Saputra; Aris Suziman (CV. Gerasi Insan Nusantara, 2025)
Listening is a fundamental language skill that elementary school students need to develop; however, the listening skills of fourth-grade students at SD Negeri 2 Konda were still relatively low. Students experienced difficulties in understanding story content, identifying the main idea, answering questions based on information they heard, and drawing conclusions from the stories. This condition was associated with learning practices that remained largely dominated by lecture-based instruction and the limited use of engaging learning media, resulting in suboptimal student engagement during listening activities. This study aimed to determine the effect of an interactive storytelling method based on learning videos on the listening skills of fourth-grade students at SD Negeri 2 Konda. The study employed a quantitative approach with a pre-experimental design using a One-Group Pretest–Post-test Design. The research participants consisted of 30 fourth-grade students selected through saturated sampling. Data were collected through listening skill tests, observations, and documentation and were analyzed using descriptive and inferential statistics, including the Shapiro–Wilk normality test and a paired-samples t-test. The results showed that the mean listening skill score increased from 63.53 on the pretest to 78.90 on the post-test. The paired-samples t-test produced a significance value of 0.000 (<0.05), indicating that H₀ was rejected and H₁ was accepted. These findings demonstrate that the interactive storytelling method based on learning videos had a significant effect on the listening skills of fourth-grade students at SD Negeri 2 Konda. Accordingly, this method can serve as an alternative instructional approach for Indonesian language learning in elementary schools.